Research trends and hotspots of neuropathic pain in neurodegenerative diseases: a bibliometric analysis - Fu, Yujie; Gong, Chan; Zhu, Chenchen; Zhong, Weiquan; Guo, Jiabao; Chen, Binglin (Frontiers in Immunology, 2023)
Background Neuropathic pain is caused by a neurological injury or disease and can have a significant impact on people’s daily lives. Studies have shown that neuropathic pain is commonly associated with neurodegenerative diseases. In recent years, there has been a lot of literature on the relationship between neuropathic pain and neurodegenerative diseases. However, bibliometrics is rarely used in analyzing the general aspects of studies on neuropathic pain in neurodegenerative diseases. Methods The bibliometric analysis software CiteSpace and VOSviewer were used to analyze the knowledge graph of 387 studies in the Science Citation Index Expanded of the Web of Science Core Collection Database. Results We obtained 2,036 documents through the search, leaving 387 documents after culling. 387 documents were used for the data analysis. The data analysis showed that 330 papers related to neuropathic pain in neurodegenerative diseases were published from 2007–2022, accounting for 85.27% of all published literature. In terms of contributions to the scientific study of neuropathic pain, the United States is in the top tier, with the highest number of publications, citations, and H-indexes. Conclusion The findings in our study may provide researchers with useful information about research trends, frontiers, and cooperative institutions. Multiple sclerosis, Parkinson’s disease, and Alzheimer’s disease are the three most studied neurodegenerative diseases. Among the pathological basis of neurodegenerative diseases, microglia-regulated neuroinflammation is a hot research topic. Deep brain stimulation and gamma knife radiosurgery are two popular treatments.